Atypical antipsychotic therapy in Parkinson's disease psychosis: A retrospective study. Issue 6 (14th April 2017) - Yuan, Mei; Sperry, Laura; Malhado‐Chang, Norika; Duffy, Alexandra; Wheelock, Vicki; Farias, Sarah; O'Connor, Kevin; Olichney, John; Shahlaie, Kiarash; Zhang, Lin
Abstract: Objective: Parkinson's disease psychosis (PDP) is a frequent complication of idiopathic Parkinson's disease (iPD) with significant impact on quality of life and association with poorer outcomes. Atypical antipsychotic drugs (APDs) are often used for the treatment of PDP; however, their use is often complicated by adverse drug reactions (ADRs). In this study, we present patients with PDP who were treated with the most commonly used atypical antipsychotic agents and review their respective ADRs. Methods: A retrospective study was carried out to include a total of 45 patients with iPD who visited a movement disorders clinic between 2006 and 2015. All PDP patients treated with atypical APDs were included in the analysis for their specific ADRs. Results: Forty‐five iPD patients (mean age of onset: 62.67 ± 9.86 years) were included, of those 10 patients had psychosis (mean age of onset: 76.80 ± 4.61 years). Of the 45 patients, 22.2% were found to have psychotic symptoms, of whom 70% had hallucinations, 20% had delusions, and 10% illusions. Seventy percent of psychotic symptoms occurred after ten or more years from diagnosis of iPD. PDP patients were treated with quetiapine, olanzapine, and risperidone separately or in combination, all of which were found to have certain ADRs. Limitations: This study was limited by its retrospective study design and small sample size and with likely selection bias. Conclusions: The prevalence of PDP is relatively high in older patients with iPD. The uses of the currently available atypical APDs in this patient population are often complicated by ADRs. The selective 5‐HT2A  inverse agonist, pimavanserin, could be a better alternative in the treatment of PDP. Abstract : Parkinson's disease psychosis (PDP) remains a pronounced therapeutic challenge. Atypical antipsychotic was often accompanied by adverse drug reactions. Pimavanserin could be a better alternative in the treatment of PDP.